NanoMOFs: little crystallites for substantial applications. Issue 17 (18th April 2018) - Majewski, M. B.; Noh, H.; Islamoglu, T.; Farha, O. K.
Abstract : Synthetic methods for the preparation of metal–organic framework crystallites in the nano-size regime and their potential applications are reviewed. Abstract : In order to tailor metal–organic framework (MOF) materials for a myriad of potential applications, recent studies have expanded on the advantages of using MOF particles in the nano-size regime. These so-called nanoMOFs may be prepared using a variety of synthetic methodologies; many analogous to those used for the preparation of their bulk counterparts. However, many of these techniques lack the refinement to consistently produce monodisperse particle sizes. Here we discuss recent advances in some of these synthetic methods with a particular emphasis on methods exhibiting increased levels of size-control while producing crystallites ranging in size from tens to hundreds of nanometers. Additionally, we highlight some specific applications that benefit from the inherent properties of nano-sized MOFs.